Neonicotinoid insecticides in river water of an agriculture-dominated basin: Occurrence, flux variations, and ecological risks - Wang, JinZe; Hou, Jie; Han, BingJun; Wang, LiXi; Zhu, ZiYang; Liu, WenXin (Marine pollution bulletin, 2025)
The widespread use of neonicotinoid insecticides (NNIs) has led to their widespread detection in surface waters worldwide. However, pollution characteristics and transport fluxes in agriculture-dominated watersheds have not been thoroughly studied. In this study, we analyzed the pollution characteristics of NNIs in the Zhoukou Reach of the Shaying River, a typical agricultural area in northern China, focusing on their vertical distribution, transport flux, and ecological risk across different river sections. NNIs were commonly detected in the surface water in the Zhoukou section of the Shaying River, with concentrations ranging from 42.5 to 307 ng/L. The predominant compounds were imidacloprid, thiamethoxam, acetamiprid, and clothianidin at concentrations of 33.4 ng/L, 30.0 ng/L, 29.1 ng/L, and 28.7 ng/L, respectively. Vertically, higher NNI concentrations of 163 ± 88.9 ng/L were found in the bottom layer than in the surface layer (152 ± 82.9 ng/L) (p < 0.05). Compared to the upstream and midstream regions, the NNI concentration downstream was higher, primarily because of the developed fruit cultivation and high pesticide usage. The initial input flux of NNIs of the Zhoukou section of the Shaying River was 1.73 kg/d, whereas the output flux was 4.32 kg/d, with a net flux of 2.58 kg/d. In the midstream and upstream regions, NNIs pose a chronic risk to aquatic invertebrates, whereas NNIs in the downstream region present an acute risk. Therefore, it is crucial to alleviate downstream NNI pollution. [Display omitted] •NNIs were frequently detected in river water in agricultural area (152 ± 82.9 ng/L).•Bottom layer suffered from higher NNIs pollution than surface layer.•Agricultural industry layouts affected the spatial distribution of NNIs.•Riverine NNIs fluxes increased from 1.73 kg/d to 4.32 kg/d from inlet to outlet.